Can functional emotion regulation protect children's mental health from war trauma? A Palestinian study. (19th April 2017) - Diab, Marwan; Peltonen, Kirsi; Qouta, Samir R.; Palosaari, Esa; Punamäki, Raija‐Leena
Abstract : Effective emotion regulation (ER) is expected to protect mental health in traumatic stress. We first analysed the protective (moderator) function of different ER strategies and the associations between ER and mental health. Second, we tested gender differences in the protective function of ER and the associations between ER strategies and mental health. Participants were 482 Palestinian children (girls 49.4%; 10–13 years, M = 11.29, SD = .68) whose ER was assessed by the Emotion Regulation Questionnaire and mental health by post‐traumatic stress (Children's Impact Event Scale), depressive, and psychological distress (Strengths and Difficulties Questionnaire) symptoms, and by psychosocial well‐being (Mental Health Continuum‐Short Form). War trauma involved 42 events. Results showed, first, that none of the ER strategies could protect a child's mental health from negative impact of war trauma, but self‐focused ER was associated with low depressive symptoms, and other‐facilitated ER with high psychological well‐being. However, controlling of emotions formed a comprehensive risk for children's mental health. Second, gender differences were found in the protective role of ER, as self‐focused and distractive ER formed a vulnerability among boys. The results are discussed in the context of emotional and regulative demands of war and life‐threat.